Following the footsteps of the contextualization of architecture and urban landscape - Bernal, Amparo (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2013)
This text intends to approach the study of the evolution of urban landscape in Spain during the sixties, following the footprints of architectural journals: texts and illustrations that accompanied the contemporary intellectual debate on the architecture built in the suburbs of Madrid and Barcelona. Fifty years later, this stage of the city planning has been overcome. Even the architecture and the empty spaces that emerged in the outskirts of the large cities, unconnected to a particular tradition or a specific place, have been integrated in the urban landscape, thanks to the sociological dimension of the urbanism and to the basic human need to identify and accept the natural environment. This story is constructed on the basis of the testimony of those architects who had a direct responsibility in resolving the problem of urban planning and dwelling in that decade in Spain. Their approach found his best narrative screenplay through photographs published in architecture reviews.
Keywords: Architecture; urbanism; photography